Knowledge sharing behavior as mediating role on openness to experience and innovative work behavior - Zuhdi, Haidar; Etikariena, Arum (Goodwood Publishing, 2022)
Purpose: This study aimed to examine the mediating effect of knowledge sharing behavior on the relationship between openness to experience and innovative work behavior on students at the University of Indonesia. Research methodology: Quantitative approach with a cross-sectional study was employed for the research. The study population consisted of 306 students in Universitas Indonesia. Data were elicited through a questionnaire with convenience sampling technique while the analysis was carried out using PROCESS by Hayes. Results: The results of this study revealed that knowledge sharing behavior has a partially mediating role in the relationship between openness to experience and innovative work behavior. Limitations: The challenge was the unevenness sample from each faculty, most of the students selected for the study through a random method were from the Faculty of Psychology. This could affect the generalizability of the findings. Contribution: The results of this study can be used as a reference for training innovation programs that will be given to Universitas Indonesia students for the purpose of making them better prepared to innovate.